Two case studies of community language learning with possible implications for the natural order hypothesis - Parker, Ray (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1991)
This article sets out to describe two experimental series of community language learning—type sessions and to examine the data generated by them in terms of the realisations of functions focused on during them. It goes on to discuss implications that this may have for the natural order hypothesis. It begins with brief descriptions of both the methodology and the hypothesis.